2012
DOI: 10.1016/j.ajo.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Diabetic Microaneurysms by Simultaneous Fluorescein Angiography and Spectral-Domain Optical Coherence Tomography

Abstract: PURPOSE To correlate spectral domain optical coherence tomography (SD-OCT) findings of perfused diabetic microaneurysms with leakage status on fluorescein angiography (FA) using simultaneous FA and SD-OCT. DESIGN Retrospective, observational case series. METHODS 173 microaneurysms were analyzed in 50 eyes (14 mild nonproliferative diabetic retinopathy (NPDR); 22 moderate NPDR; 9 severe NPDR; 5 proliferative diabetic retinopathy (PDR)) of 40 diabetic patients using simultaneous FA and SD-OCT. The characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 8 publications
6
37
0
Order By: Relevance
“…27-29 Two recent OCTA studies showed that microaneurysms are more often found in the DCP than in the SCP. 11, 24 It will be important to reassess these findings as they relate to the MCP, since these studies have used the preset, INL-splitting segmentation boundaries to study the location of microaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…27-29 Two recent OCTA studies showed that microaneurysms are more often found in the DCP than in the SCP. 11, 24 It will be important to reassess these findings as they relate to the MCP, since these studies have used the preset, INL-splitting segmentation boundaries to study the location of microaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Characterization of individual microaneurysms in DME following focal laser photocoagulation may increase our understanding of microaneurysm regression and provide insight to improve treatment approaches. In this study, we characterized individual microaneurysms in DME using simultaneous FA and SD-OCT following navigated focal laser photocoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the relationships between OCT and FA findings have been explored and the various characteristics related to each other indicating that both overlap and the complementarity of findings [13,14] . Simultaneous FA and SD-OCT allow improved characterization of DME features and allow distinction of perfused MA from nonperfused MA as well as the ability to localize fluid to different retinal layers [15] . In a recent study, abnormalities of choroidal perfusion were detected by indocyanine green angiography, and the combination of this imaging modality along with enhanced-depth OCT imaging and FA were reported as superior indicators of ocular perfusion status in diabetic eyes [16] .…”
Section: Evidencementioning
confidence: 99%